Perception of Female Surgical Residents of Their Training in the Examination of Male Genitalia in Makkah Hospitals, KSA - Rani A. Al-Sairafi; Sameer A. Softa; Aisha E. Ahmed; Elbagir A. Elfaki (New Horizons in Medicine and Medical Research Vol. 8, 2022)
The present study aims to assess the perception and confidence of female surgical residents in clinical examination of inguinal hernia and intimate of opposite sex in five hospitals, Makkah holy city. Study also sought to shed light on the barriers and the impact of different teaching modalities that are currently used in undergraduate education. Despite clear cultural limits and religious traditions, deficiencies in the clinical examination abilities of female surgical residents of the male groyne hernia and genitalia have not been addressed or investigated in the Arab and Muslim populations. The kids’ ethnic backgrounds have also influenced their future training and skills. Due to their sensitive nature, many systems’ examinations for patients are considered particularly sensitive to execute by students and professionals of both sexes. Methods: A cross-sectional design based on a self-administered questionnaire which was distributed to 80 female surgical resident trainees across five Hospitals in Makkah, Holy city, Saudi Arabia. The study was carried out between the period of September 2020 to July 2021 and involved all the female surgical residents from level 1 - 5 (R1 to R5). Result: Our study showed that overall perception of most of female residents on their performance on clinical examinations is less than expected. This study revealed that the main factor affecting the female resident’s clinical examination of the opposite sex intimate is the gender difference. 56 (81.2%) participants stated that their gender impacted their confidence and skills in examination of intimate of opposite sex, while 13 (18.8%) stated that gender has no effect. Conclusion: Gender effects medical student clinical learning in a conservative culture in a variety of ways, including clinical exposure, supervisor support, patient willingness and consent, and some undergraduate methods of learning clinical skills that are not linked with postgraduate demands.